Social Support and Individual Support for Bullying Prevention among Adolescents in the School: A Systematic Review - Ubudiyah, Masunatul; Nursalam, Nursalam; Sukartini, Tintin (International Journal of Psychosocial Rehabilitation, 2020)
The number of bullying incidents has increased, primarily in adolescents at school; it has a negative impact on the physical and mental health of students. This study aims to provide social support and individual support for bullying prevention of the adolescent at school. The study uses a systematic review with the preferred reporting items for Systematic Reviews and Meta-Analysis (PRISMA) approach. A literature search was conducted in Scopus, ScienceDirect, and ProQuest databases. The search utilized the Boolean phrases “bullying OR aggression” and “adolescent” and “school” with publication limitation of 2015 until 2019. The subject of this study was adolescent victim without specific ages and classification at school. One of the interventions carried out is to increase social activities involving students. The systematic review finally identified nine articles from 209 articles that were most relevant to this study. The result showed that the prevention of bullying at school was influenced by social-supportiveness and individual support. In terms of the intervention most effective in dealing with bullying at school, the results of this review suggest the importance of collaboration; all of the elements of school, teachers, and school regulation are key to suppress bullying in an adolescent.